(untitled) (Research, Society and Development, 2022)
In Mozambique, cashew crop cultivation is practiced by both family and commercial sectors. However phytosanitary problems have been found to inflict production and productivity in both sectors and are mainly due to the diseases caused by fungi. Adoption of appropriate disease control measures translates into benefits to the national economy resulting from production increases and subsequent increases in export volumes. However, the knowledge of effective disease control approaches requires the testing of various control methods. Thus, the present study was intended to objectively assess the effectiveness of Coprox Super 85% WP (Copper Oxychloride 850g/kg) e Starback 25% SC (Flutriafol 250 g/l) for the control of cashew leaf and fruit blight fungi complex. The growth media PDA in Petri dishes was amended with fungicides and then centrally inoculated with mycelial discs. Mycelial growth of individual fungal isolates was assessed by measuring two perpendicular diameters and these were later used to calculate the growth rate and inhibition percentage. Flutriafol had higher control effectiveness against cashew leaf and fruit blight fungi than copper oxychloride and is therefore recommended for field trials.